2019
DOI: 10.21203/rs.2.11281/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of First Line Antiretroviral Treatment Failure among Patients on Highly Active Antiretroviral Therapy in selected Public Hospitals Jimma, Southwest Ethiopia a Case Control Study

Abstract: Background: Highly Active Antiretroviral Therapy (HAART) has substantially declined morbidity and mortality related to Human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS). Despite this fact, first-line ART failure has emerged as a growing concern. However, factors associated with first-line ART failure are not well empathized and studied. Hence, we aimed to identify the determinants of first-line ART failure among patients attending ART in Public Hospitals Jimma, Southwest Ethiopia. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…In addition, the odds of virological failure were higher among those who had a history of OI throughout the follow-up period compared with those who had no history of OI throughout the follow-up period. This finding is in line with the studies conducted in Jimma ( 17 ) and Arba Minch towns of Ethiopia ( 35 ) which showed patients with opportunistic infections, such as TB, appear to be at a higher risk of virological failure. This finding also consisted of a study conducted in Nigeria ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the odds of virological failure were higher among those who had a history of OI throughout the follow-up period compared with those who had no history of OI throughout the follow-up period. This finding is in line with the studies conducted in Jimma ( 17 ) and Arba Minch towns of Ethiopia ( 35 ) which showed patients with opportunistic infections, such as TB, appear to be at a higher risk of virological failure. This finding also consisted of a study conducted in Nigeria ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the odds of virological failure among those who had a history of substance use were higher compared with those who had no history of substance use. This finding is supported by the study conducted at Jimma (17), Addis Ababa (25), and Vietnam (26). This might be since using HAAT drugs and substances simultaneously would be prone to mental health problems resulting in poor adherence characterized by failure to take medication properly; moreover, interrupting the medication which leads finally to first-line ART treatment failure (27).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The patients who had failed for fist-line drug are 46% more likely to fail again for second-line drugs and are attributed to the higher number of side effects and have greater likelihood of experiencing drug resistance and treatment fatigue as a result of being on treatment longer [5]. Previous studies reported that various factors including being male gender, illiterate, widower, poor adherence and treatment interruption, WHO clinical stage III and/or IV, low CD4 cell at ART initiation, presence opportunistic infections, low BMI, taking ARV regimen before ART initiation, taking Stavudine and Zidovudine (AZT) based regimen, TB coinfection, substance use and longer duration on ART were significantly associated with first line ART failure [6]. The World Health Organization cites poor access to services, complex drug regimens, pregnancy, mental health disorders, substance abuse, and weak social support as major barriers to adherence [7].…”
Section: Introductionmentioning
confidence: 99%